MicroRNAs and their putative targets in Brassica napus seed maturation - Huang, Daiqing (BioMed Central, 2013)
BACKGROUND: MicroRNAs (miRNAs) are 20–21 nucleotide RNA molecules that suppress the transcription of target genes and may also inhibit translation. Despite the thousands of miRNAs identified and validated in numerous plant species, only small numbers have been identified from the oilseed crop plant Brassica napus (canola) – especially in seeds. RESULTS: Using next-generation sequencing technologies, we performed a comprehensive analysis of miRNAs during seed maturation at 9 time points from 10 days after flowering (DAF) to 50 DAF using whole seeds and included separate analyses of radicle, hypocotyl, cotyledon, embryo, endosperm and seed coat tissues at 4 selected time points. We identified more than 500 conserved miRNA or variant unique sequences with >300 sequence reads and also found 10 novel miRNAs. Only 27 of the conserved miRNA sequences had been previously identified in B. napus (miRBase Release 18). More than 180 MIRNA loci were identified/annotated using the B. rapa genome as a surrogate for the B.napus A genome. Numerous miRNAs were expressed in a stage- or tissue-specific manner suggesting that they have specific functions related to the fine tuning of transcript abundance during seed development. miRNA targets in B. napus were predicted and their expression patterns profiled using microarray analyses. Global correlation analysis of the expression patterns of miRNAs and their targets revealed complex miRNA-target gene regulatory networks during seed development. The miR156 family was the most abundant and the majority of the family members were primarily expressed in the embryo. CONCLUSIONS: Large numbers of miRNAs with diverse expression patterns, multiple-targeting and co-targeting of many miRNAs, and complex relationships between expression of miRNAs and targets were identified in this study. Several key miRNA-target expression patterns were identified and new roles of miRNAs in regulating seed development are suggested. miR156, miR159, miR172, miR167, miR158 and miR166 are the major contributors to the network controlling seed development and maturation through their pivotal roles in plant development. miR156 may regulate the developmental transition to germination.